THE INFLUENCE OF KNOWLEDGE, MOTIVATION, AND INVESTMENT RISK ON INTEREST IN INVESTING IN THE AJAIB MUTUAL FUND APPLICATION - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2024)
Otoritas Jasa Keuangan (OJK) has the ability to assist the Indonesian Stock Exchange (BEI) in disseminating information about convenient speculation applications and focusing efforts. Based on the source katadata.co.id, the Ajaib application is ranked second among the most well-known investment applications in Indonesia with a rating of 80%. One of the reasons why people decide to use the Ajaib speculation application is because this application provides examples of different businesses from beginners to experienced. Therefore, researchers are interested in studying the factors that influence investment interest in the Ajaib mutual fund application. This researcher used 3 independent variables in this research, including investment knowledge, investment motivation, and investment research. Information was collected in this research through distributing questionnaires. The population in this research is all residents who have invested using the Ajaib mutual fund application. The number of respondents used in this research was 100 respondents. The analytical procedure used in this research uses multiple linear regression analysis. The research results show that investment knowledge does not have a partial effect on respondents' investment interest in the Ajaib mutual fund application. Meanwhile, investment motivation and risk have a partial effect on respondents' interest in investing in the Ajaib mutual fund application. Finally, researchers found that the three independent variables (investment knowledge, investment motivation, investment risk) simultaneously influenced respondents' investment interest in the Ajaib mutual fund application.